A multi-method approach to investigating porous media cooling for enhanced thermal performance of photovoltaic panels: exploring the effects of porosity, flow rates, channel design, and coolant types - Masalha, Ismail; Masuri, Siti Ujila; Badran, Omar; Alahmer, Ali (Elsevier, 2025)
Elevated temperatures in photovoltaic (PV) panels adversely affect their efficiency and lifespan, necessitating effective cooling strategies. This study introduces a novel approach by integrating porous media within cooling channels to improve thermal management and energy output. While several cooling techniques have been explored, the integration of porous media with various coolants and their combined effects on cooling channel design, porosity size, flow rates, and porous media type have not been thoroughly investigated. This study fills this gap by conducting both experimental and numerical investigations to analyze key parameters, including porosity size (0.35–0.5), flow rates (1–4 L/min), cooling channel design, and coolant types (water, chemical alcohol, engine oil). Experimental tests were performed on 30-watt polycrystalline PV cells under real-world conditions, employing porous media such as gravel, marble, flint, and sandstone. The study was structured into three phases: (1) a comparative analysis of cooling performance with and without porous media, (2) optimization of porosity size for enhanced cooling, and (3) identification of optimal flow rates for system efficiency. The study identified optimal configurations, achieving up to 35.7 % temperature reduction and a 9.4 % power output increase with a porosity size of 0.35 and a flow rate of 2 L/min. ANSYS simulations validated experimental findings, with deviations in PV surface temperature below 3 %. Simulations further revealed that a tapered cooling channel design (5 mm inlet to 3 mm outlet), combined with water as the coolant and sandstone as the porous medium, reduced PV temperatures to 36.6 °C. This comprehensive analysis highlights the potential of porous media-integrated cooling systems to enhance PV panel performance and longevity.